THE INFLUENCE OF FIXED ASSET INVESTMENTS, SOLVENCY ON THE PROFITABILITY OF MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE PERIOD 2017-2020 - Sasmiharti, Juni (Finance : International Journal of Management Finance, 2024)
This research aims to investigate the effect of fixed asset investment and solvency level on the profitability of manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2020 period. Through analysis of company financial data, this research obtained significant findings regarding the relationship between these variables. The research results show that fixed asset investment has a positive influence on the profitability of manufacturing companies. Companies that are able to make efficient investments in fixed assets tend to achieve increased profitability because they can increase production capacity and operational efficiency. Furthermore, the company's solvency level is also proven to influence profitability. Companies with a balanced level of solvency tend to have better financial stability, which supports profitability growth. In the context of economic and policy changes in the 2017-2020 period, this research highlights the importance of understanding external factors that can influence the relationship between fixed asset investment, solvency and profitability.